Genetic divergence and evaluation of yield potential of Jatropha curcas accessions collected from Peninsular Malaysia - Arolu, Ibrahim Wasiu; Yusop, Mohd Rafii; Musa, Mohamed Hanafi; Tengku Muda Mohamed, Mahmud; Askani, S. (Universiti Putra Malaysia Press, 2015)
Widening of the narrow genetic base of Jatropha curcas through germplasm collection, diversity study and evaluation is needed to bring about much needed improvement in its seed yield and oil content. This study was carried out to profile the divergence patterns of 45 Jatropha curcas from three populations (Kelantan, Selangor and Terengganu) and to evaluate their yield over a period of three years. Eleven (11) morphological traits together with ISSR markers were used in this study. The percentage of polymorphism for the ISSR markers among the three populations was very high, ranging from 90.38-100%. Shannon information index (I) and expected heterozygosity (He) were found to be highest in the Kelantan population, at 0.58 and 0.40 respectively. Genetic differentiation (Analysis of molecular variance) expressed as fixation index (0.46) revealed that variations within the population accounted for about 100% of the total variation. Interestingly, the cluster analysis based on molecular and morphological traits, as presented in the dendrogram, grouped the 45 accessions into seven and five clusters respectively. For morphological traits, variability in terms of coefficient of variation (CV) was very high, as much as 53.19 and 51 % in total number of seeds and oil yield/ha. Small differences were seen between phenotypic and genotypic coefficient of variation (≤ 10%) for the yield trait. Broad sense heritability for virtually all the yield and yield components was very high (≥ 67.8). Accessions B-01- 03, D-01-06, T-01-06, B-06-02 have been identified and recommended for further evaluation under field conditions before they are chosen for future breeding programmes for seed yield and oil improvement.